1996
DOI: 10.1021/ja9624331
|View full text |Cite
|
Sign up to set email alerts
|

The First Unequivocal Evidence of the Reacting Electrophile in Aromatic Acylation Reactions1

Abstract: The acylation of aromatic compounds with aroyl triflates can be performed in organic solvents (1,2-dichloroethane) without Friedel−Crafts catalysts. These reaction conditions allow kinetic investigations of the reaction in homogeneous solution. From rate measurements evidence is given that in all cases the aroyl triflates 1, 6, and 11 dissociate primarily into the corresponding acylium ions which subsequently react with the aromatic compounds. The rate-determining step, either the dissociation of the aroyl tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 37 publications
1
45
0
1
Order By: Relevance
“…O-Activation of the vinylogous amide group in 59 was then investigated with an electrophilic agent distinct from Tf 2 O in order to preclude any possibility of nucleophilic exchange involving the transient iminium intermediate (see above). As a result, the highly reactive acyl electrophile, pivaloyl triflate, generated in situ by the reagent combination of pivaloyl chloride and AgOTf, [73] proved suitable for this purpose. Subsequent desilylation with TBAT led to azomethine ylide formation (60) and cycloaddition with phenyl vinyl sulfone, affording the spirofused pyrrolidine 62 (77 %) as a single constitutional stereoisomer.…”
Section: Resultsmentioning
confidence: 99%
“…O-Activation of the vinylogous amide group in 59 was then investigated with an electrophilic agent distinct from Tf 2 O in order to preclude any possibility of nucleophilic exchange involving the transient iminium intermediate (see above). As a result, the highly reactive acyl electrophile, pivaloyl triflate, generated in situ by the reagent combination of pivaloyl chloride and AgOTf, [73] proved suitable for this purpose. Subsequent desilylation with TBAT led to azomethine ylide formation (60) and cycloaddition with phenyl vinyl sulfone, affording the spirofused pyrrolidine 62 (77 %) as a single constitutional stereoisomer.…”
Section: Resultsmentioning
confidence: 99%
“…Their application to the Fries rearrangement of various phenyl carboxylate derivatives also results in high yield. The mixed carboxylic trifluoromethanesulfonic anhydride is formed from the reaction of TfOH with acyl chloride [65] or carboxylic acid [66,67]. It is known as an extremely powerful acylating agent [65,67]; its reaction with toluene is highly selective when a bulky side chain is used [67].…”
Section: Special Features Of Tfoh In Selective C-and/or O-acylationsmentioning
confidence: 99%
“…Several plausible routes using various active species [65][66][67] for aromatic acylation exist (Scheme 15). The mixed carboxylic trifluoromethanesulfonic anhydride may be obtained by treatment of TfOH with acyl chloride [65] or carboxylic acid [66,67]. The acylation pathway for an acyl donor in the form of alkyl carboxylic acid 113 or acyl chloride 114 can produce several species.…”
Section: Multifunctional Features Of Deuterated Tfoh (Tfod)mentioning
confidence: 99%
“…Both dimethoxybenzenes easily undergo electrophilic substitution reaction by active cationic species. 34 Nitrenium ion has long been known to react even with benzene or toluene to form a diarylamine, [35][36][37][38] or with water to form p-aminophenol. 39 Our attempted polymerization experiments with N-arylhydroxylamines (below) have also confirmed that nitrenium ion is a reactive species which is difficult, if not impossible, to be used as an intermediate to form clean polymers.…”
Section: Polymerization Of Aniline In the Presence Of Electron-rich Amentioning
confidence: 99%